Keragaman Genetika Xanthomonas axonopodis pv. glycines Asal Kedelai Varietas Edamame di Indonesia - Andi Khaeruni; Antonius Suwanto; Budi Tjahjono; Meity S. Sinaga (Jurnal Perlindungan Tanaman Indonesia, 2007)
Xanthomonas axonopodis pv. glycines cause bacterial pustule disease caused a serious disease in Edamame cultivation in Indonesia. We collected a total of 29 X. axonopodis pv. glycines isolates from Edamame fields at Jember, Ciawi, Cipanas and Bogor. The genetic diversity analysis of all isolates employing ARDRA and ISR technique showed six and seven different DNA profile, respectively. Therefore there are at least seven strains of X. axonopodis pv. glycines infected Edamame in Indonesia. Both CPI from Cipanas and JA4 from Sukorejo Jember isolates possess unique DNA profle and genetically are not closely related to other isolates.